치위생과 학생들의 임상실습만족도가 치과위생사 이미지에 미치는 영향 - 한양금; Yang Keum Han; 김한홍; Han Hong Kim (Chiwisaeng gwahakoeji, 2015)
본 연구는 치위생전공 대학생의 임상실습 만족도와 치과 위생사 이미지의 관계를 파악하고 치과위생사 이미지에 영향을 미치는 요인을 파악하기 위해 수행되었다. 연구대상은 편의 추출된 대전광역시, 울산광역시 및 충청북도에 소재하는 대학의 치위생과에 재학 중인 706명의 학생을 대상으로 하였으며, 자료는 구조화된 설문지를 이용하여 2014년 10월 20일부터 2015년 4월 13일까지 수집하였다. 주요 결과는 다음과 같다. 연구대상자의 임상실습 만족도 평균은 3.32±0.46점, 치과위생사 이미지의 평균은 3.55±0.42점이었다. 일반적 및 실습관련 특성에 따른 임상실습 만족도와 치과위생사 이미지의 차이를 분석한 결과는 임상실습 만족도는 전공 만족도가 높을수록(p=0.003) 통계적으로 유의하게 나타났으며, 치과위생사 이미지는 학년이 높을수록 (p=0.013), 전공 만족도가 높을수록(p＜0.001), 실습경험 횟수가 많을수록(p=0.009), 실습기관 형태가 병원급 일수록 (p=0.003), 입학 동기는 적성이 맞거나 치과위생사에 대한 깊은 인상이 되어 있는(p=0.039) 경우 통계적으로 유의하게 나타났다. 임상실습 만족도와 치과위생사 이미지 간의 상관 분석 결과는 정적 상관관계를 보였으며, 치과위생사 이미지에 영향을 미치는 관련 변수로는 실습횟수(p=0.009), 실습 기관 형태(p=0.003), 임상실습 만족도(p＜0.001)가 영향을 미치는 요인으로 나타났다. 결론적으로 치위생 전공 학생들이 학교생활에서 자신의 전공 분야에 대한 실습 경험이 자신의 직업에 미치는 긍정적 이미지 함양을 위한 임상 실습 지도안을 마련하고 임상실습 후 자신의 부족한 분야에 대한 보완이 이루어질 수 있도록 학생지도를 위한 기초 자료로 활용될 수 있을 것으로 생각된다. The purpose of this study was to examine the relationship between image of dental hygienists and clinical practice satisfaction of dental hygiene students. The subjects in the study were 706 female students who majored in dental hygiene at randomly selected colleges, which were located in Daejeon, Ulsan, and North Chungcheong province. Data were gathered using structured questionnaires from October 20, 2014 to April 13, 2015. The major findings of the study were as follows: The average of satisfaction with clinical practice was 3.32, The average of image of dental hygienists was 3.55. As for clinical practice satisfaction by general and practice characteristics, there were statistically significant difference according to degree of satisfaction for major, as for image of dental hygienists, there were statistically significant difference according to grade, degree of satisfaction for major, number of clinical experience, practice organization and admission motive. The relationship of image of dental hygienists and clinical practice satisfaction was analyzed, and clinical practice satisfaction had a significant positive effect on image of dental hygienists. As a result of analyzing which variables affected image of dental hygienists, it’s found that image of dental hygienists were under the influence of number of clinical experience, practice organization and clinical practice satisfaction. Clinical practice satisfaction influenced image of dental hygienists. Therefore, dental hygiene students are given a chance to have positive image through well-structured clinical practice.